Selected aspects of apoptosis in psoriasis - Hanna Myśliwiec; Anna Baran; Iwona Flisiak (Termedia Publishing House, 2017)
Apoptosis is a physiological mechanism of programmed cell death, in contrast to necrosis, without eliciting an inflammatory response. It plays the key role in the functioning of different tissues and organs. The balance between proliferation and apoptosis of keratinocytes is important for epidermal maintenance of homeostasis. Dysfunctional apoptosis plays an important role in the development of several skin disorders. Diseases with an increase of apoptosis are usually acute, while those with inhibited apoptosis tend to be chronic. Psoriasis is an immune-mediated chronic inflammatory skin disease. It is characterized by keratinocyte hyperproliferation and abnormal differentiation. Psoriatic keratinocytes are resistant to apoptosis and this phenomenon can be the key event in psoriatic hyperplasia. Apoptosis disturbances can also affect immune cells involved in the pathogenesis of psoriasis. In this review, we describe the basic concept of apoptosis and its relevance in psoriatic pathogenesis.